2021
DOI: 10.3389/fneur.2021.704639
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of NF1 Gene Mutations and Genetic Modifiers in Neurofibromatosis Type 1

Abstract: Neurofibromatosis type 1 (NF1) is a tumor predisposition genetic disorder that directly affects more than 1 in 3,000 individuals worldwide. It results from mutations of the NF1 gene and shows almost complete penetrance. NF1 patients show high phenotypic variabilities, including cafe-au-lait macules, freckling, or other neoplastic or non-neoplastic features. Understanding the underlying mechanisms of the diversities of clinical symptoms might contribute to the development of personalized healthcare for NF1 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 123 publications
(162 reference statements)
0
16
0
Order By: Relevance
“…NF1 ). 19 , 20 We first retrieved NGS sequencing data for CPGs that are firmly associated with CRC. Thereafter, irrespective of the clinical picture, the entire panel was interrogated, and both PVs and variants of uncertain significance (VUS) were annotated.…”
Section: Methodsmentioning
confidence: 99%
“…NF1 ). 19 , 20 We first retrieved NGS sequencing data for CPGs that are firmly associated with CRC. Thereafter, irrespective of the clinical picture, the entire panel was interrogated, and both PVs and variants of uncertain significance (VUS) were annotated.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the influence of variants in other genes on NF1 phenotype cannot be excluded. Several studies showed that different mutations of NF1 and related genetic modifiers might contribute together to clinical features in NF1, including tumor development, making the scenario more complex [ 119 ]. It will be very important to perform this analysis in our cohort of patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the employed panel, high-penetrance genes involve a lifetime risk of cancer >= 40%, while the risk associated with “moderate” genes is usually <40%, although this notion does not invariably apply to fully penetrant methylated CpG islands (CpGs) (e.g., NF1 ) [ 25 ]. We first retrieved NGS sequencing data for CpGs that were strongly associated with PDAC, and both PVs and VUS were annotated.…”
Section: Methodsmentioning
confidence: 99%